Implementation of Islamic Religious Education Learning on the Social Transformation Attitudes of Students at the Bumi Sholawat Safinatun Najaa Islamic Boarding School, Central Lampung - M. Chadziqul Faruq; Ehwanudin; M. Saidun Anwar (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This research is motivated by the importance of Islamic Religious Education (PAI) learning in shaping the social transformation attitudes of students, not only in the ritual aspect but also in their concern for the Islamic boarding school environment. PAI learning is expected to foster social awareness and collective responsibility of students through the internalization of religious values ​​in everyday life. This study aims to analyze the planning, implementation, and evaluation of PAI learning in shaping the social transformation attitudes of students at the Bumi Sholawat Safinatun Najaa Islamic Boarding School. The study used a qualitative field approach with observation, interview, and documentation techniques, as well as data analysis through reduction, presentation, and drawing conclusions. The results showed that the learning plan has included the value of social responsibility through the material of fiqh thaharah and morals, but it is still normative. The implementation of learning uses the bandongan, sorogan, lecture, and exemplary methods, but the internalization of social values ​​is still instructive. Evaluation is carried out through observation of student behavior without formal instruments. The attitude of social transformation of students is seen in participation in environmental cleanliness activities, although it is still influenced by Islamic boarding school rules. Islamic Religious Education (PAI) learning contributes to shaping the social awareness of students, but requires strengthening contextual and participatory approaches so that religious values ​​can encourage independent and sustainable changes in social behavior